2022
DOI: 10.3390/ijms23158202
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Therapeutic Effects of Apoptotic Bodies on Systemic Diseases

Abstract: Apoptosis plays an important role in development and in the maintenance of homeostasis. Apoptotic bodies (ApoBDs) are specifically generated from apoptotic cells and can contain a large variety of biological molecules, which are of great significance in intercellular communications and the regulation of phagocytes. Emerging evidence in recent years has shown that ApoBDs are essential for maintaining homeostasis, including systemic bone density and immune regulation as well as tissue regeneration. Moreover, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Current research on apoEVs in biomedical applications mostly focuses on apoptotic microvesicles [ 10 , 15 ]. However, apoptotic bodies have long been demonstrated to play an essential role in apoptosis induced immunosuppression [ 32 , 33 ]. Therefore, apoptotic bodies were not excluded from the apoEVs.…”
Section: Discussionmentioning
confidence: 99%
“…Current research on apoEVs in biomedical applications mostly focuses on apoptotic microvesicles [ 10 , 15 ]. However, apoptotic bodies have long been demonstrated to play an essential role in apoptosis induced immunosuppression [ 32 , 33 ]. Therefore, apoptotic bodies were not excluded from the apoEVs.…”
Section: Discussionmentioning
confidence: 99%
“…ApoBDs, first recognized by Kerr et al in 1972, represent large ApoVs ranging from 1 to 5 μm in diameter [ 23 ]. In the last decade, research has demonstrated their role in intercellular communication and their therapeutic effects on diseases [ 24 , 25 ]. Furthermore, ApoMVs, at 0.1–1 μm in size, were found to be physiologically different from traditional ApoBDs, possessing superior membrane integrity for molecular exchange [ 26 , 27 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Apoptotic Bodies (1–5 μm) are released by cells after a triggered collapse that results in nuclear fragmentation, increased membrane permeability and externalization of phosphatidylserine (PS). Apoptosis plays a key role in development and homeostasis ( Li et al, 2022a ). During this highly orchestrated process of cell disintegration, proteins, lipids and nucleic acids fragments are distributed in vesicles ( Crescitelli et al, 2013 ).…”
Section: Melanoma-derived Ev Heterogeneitymentioning
confidence: 99%